DataAB-JP: desenvolvimento de uma plataforma digital de monitoramento de dados em saúde na atenção básica de João Pessoa/PB - Oliveira, Ana Eloisa Cruz de (2020)
The decision-making process is essential for health management and work, and the use of tools that facilitate such a processisindispensable,such asthe Health Situation Room. In view of the difficulties perceived in the current work process methodology with the Room of Situation of Primary Care in João Pessoa - PB, creating obstacles in the decision-making process in health, the present study aims to build a digital platform to systematize and monitor health data in Primary Care in the Municipality of João Pessoa-PB. It is a methodological study of the applied type, aimed at the production of an information technology. In its first stage, a survey was carried out with health professionals, with higher education, of 74 Primary Care teams so that their perception of the current method of using the Situation Room and a possible digital format could be identified, enabling a comparative analysis between the current method of monitoring health data by Primary Care through the Situation Room, with a possible version on a digital platform. Data collection took place through a semi-structured questionnaire, applied from June to August 2019. The next step was directed towards the construction of a digital platform that could assist in the use of the Situation Room, enhancing the decision-making process. Its prototype was called DataAB-JP, and once built it was subjected to tests for evaluation by Primary Care professionals and using a questionnaire for this purpose. The entry and quality control of the data obtained were performed using Microsoft Excel software, while data analysis was performed using IBM SPSS Statistics software, version 20.0 and software R version 3.4.1. Descriptive statistics and analyzes were also used, such as: the assessment of the instrument's reliability, through the Cronbach's Alpha measure; Hypothesis testing: t-Student; and, graphs (box diagram or boxplot), in addition to the Bayesian inference of a proportion for approval of the system by health professionals. Based on the professionals' perception of the methodology for using the Situation Room and its comparison with a possible digital version, it was found that the room on the digital platform produces a higher average degree of agreement evaluated in percentage, according to the paired t-Student test. (P-Value <0.001). In other words, there is a greater convergence in the values of agreement among the Primary Care professionals interviewed in the study with regard to the Health Situation Room in its digitals format, demonstrating the preference for change to improve the work process. So the idea of computerization of the process was structured, outlining its functionalities and objectives. Once constituted, the platform was evaluated by 15 primary care health professionals for functionality, efficiency, usability and safety. Of the total responses with the maximum value of the scale adopted, 148 of the 150 possible responses reached the maximum point of agreement on the scale, making a percentage of “totally concordant” equal to 98.7%. Thus, the test showed that the professionals unanimously agreed that the platform meets the expectations for which it was created, being confirmed later through the Bayesian inference. With the use of DataAB-JP, the data from the Situation Room can be collected and stored in a more organized, safe and easily accessible way, becoming, in fact, resources capable of enhancing communication, search, and effectiveness actions of health professionals and managers. Thus, it can consolidate itself as a tool to support activities with the Health Situation Room, minimizing barriers and acting more effectively in the decision-making process.